The ever –present need for biopsy to diagnose coeliac disease safely. (July 2022) - Rai, Anuradha; Mittal, Santosh; Taneja, Kanchan; Mahajan, Nidhi
Coeliac disease (CD) is an autoimmune enteropathy which occurs in genetically predisposed individuals on exposure to gluten. The recommended diagnostic approach includes serological screening by Anti-tissue Transglutaminase antibody (anti-tTG) followed by a small intestinal biopsy. As high anti-tTG antibody is expected to be significantly associated with MARSH III histopathological changes in the small intestine, it has now become the basis for a biopsy-free approach to diagnose CD. However, we report cases of giardiasis mimicking CD both clinically and serologically; differentiation demands small intestinal biopsy.